La homogeneización biocultural desafía el ODS4. Aportes desde Latinoamérica - Alejandra Tauro; Benjamín Pujadas; Andrea Valdivia; Claudia Morales; Ricardo Rozzi (Revue Internationale des Études du Développement, 2023)
SDG4 aims to guarantee inclusive education. However, achieving this goal is problematic in the face of biocultural homogenization. This article examines the role of education in homogenization by promoting a biased representation of biodiversity based on an analysis of the visual content of textbooks in primary schools in Mexico and Chile. The results show taxonomic biases from a limited corpus of images that do not represent unique biodiversity. In Mexico, we recorded 2.5 animals for each plant studied, with 74% of native species. In Chile, the animal plant ratio was approximately 1:1, with 68% of exotic species. We discuss these biases in relation to the educational transformation that would best serve the 2030 Agenda.